Bone cement composite material with collapse resistance and preparation method thereof

By adding sodium alginate and carboxymethyl chitosan to the bone cement composite material to form a composite curing liquid, the problems of long solidification time, low compressive strength, and easy dissolution in clinical applications of bone cement composite materials have been solved, and the anti-collapse, injectability and mechanical properties of bone cement have been significantly improved.

CN119524197APending Publication Date: 2025-02-28TAIYUAN UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411593320.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing bone cement composite materials have the disadvantages of long solidification time, low compressive strength, and easy dissolution in clinical applications, which limit their application in the treatment of bone defect diseases.

Method used

By adding sodium alginate and carboxymethyl chitosan to the ordinary calcium phosphate/calcium sulfate bone cement composite material, the composite curing liquid is formed, which improves the anti-collapse, injectability and mechanical properties of bone cement.

Benefits of technology

显著提高了骨水泥的抗压强度和抗溃散性能,优化了其凝固时间和可注射性,促进了成骨细胞的附着和增殖,并在体外诱导成骨分化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524197A_ABST
    Figure CN119524197A_ABST
Patent Text Reader

Abstract

The invention discloses a bone cement composite material with collapse resistance and a preparation method thereof, and belongs to the technical field of biomedical materials. The composite material comprises a solid phase part and a liquid phase part, the liquid phase part and the solid phase part are mixed according to the liquid-solid ratio of 0.35 mL / g to 0.6 mL / g; the solid phase part is composed of calcium sulfate powder and calcium phosphate powder, and the mass ratio of the calcium sulfate powder to the calcium phosphate powder is 85: 15; the liquid phase part is selected from carboxymethyl chitosan or a combination of carboxymethyl chitosan and sodium alginate. The bone cement composite material prepared by the preparation method disclosed by the invention has good biocompatibility; due to a gel network formed by carboxymethyl chitosan and sodium alginate, the compressive strength of the bone cement is remarkably improved, and the collapse resistance and injectable performance are excellent; meanwhile, the bone cement composite material promotes the attachment and proliferation of osteoblasts, and can induce osteogenic differentiation in vitro.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bone cement composite material with anti-collapse performance and a preparation method thereof, belonging to the technical field of biomedical materials. Background Art

[0002] Bone is mineralized connective tissue that forms the locomotor system and supports daily human activities. For individuals with severe injuries and osteogenesis imperfecta, the self-healing process cannot be completed well, so clinical surgery is needed to guide bone regeneration. At present, the main methods for clinical treatment of bone defects are autologous transplantation and allogeneic transplantation, but they all have limitations and cannot guide bone regeneration well, such as: limited sources, leading to severe bone donor site damage, infection, chronic pain, and causing hematogenous diseases. Therefore, artificial bone is needed to treat bone defect diseases.

[0003] Calcium sulfate / calcium phosphate bone cement composite material has become a new type of bone replacement material due to its excellent osteoconductivity, biodegradability, plasticity, self-solidification, etc. Due to its plasticity, it is often used to solve some irregular bone defect diseases, and can be injected into the bone defect site to self-shape according to the shape of the bone defect. Therefore, it is considered to have great potential in the treatment of bone defect diseases. However, its shortcomings such as long solidification time, low compressive strength, and easy collapse limit its clinical application. Therefore, it is of great significance to develop an artificial bone transplant material that is anti-collapse, injectable, has an adjustable degradation rate, and has excellent mechanical properties. In existing studies, a large number of researchers have adopted various methods to solve the problem of anti-collapse. Chen, Huaizhi, et al. "A new injectable quick hardening anti-collapse bone cementallows for improving biodegradation and bone repair." Biomaterials Advances141 (2022): 213098.) added citric acid and chitosan to calcium phosphate cement (CPC). When the liquid-to-powder ratio (LPR) exceeded 0.4, the anti-collapse property of the bone cement slurry was slightly improved. When the LPR reached 0.8, the best performance was achieved. No obvious collapse phenomenon was found and the original shape was maintained. However, collapse occurred in the group without adding citric acid and chitosan. Wang, Kexin, et al. (Wang, Kexin, et al. "Injectable pregelatinized corn starch reinforced calcium sulfate cement for bone defect repair." Materials Letters 354 (2024): 135355.) introduced pregelatinized corn starch into calcium sulfate cement (CSC) to improve the injectability and anti-collapse of CSC. The injectability of CSC / starch reached 100%, and the shape was then kept intact in deionized water. After 60 minutes, the cement was observed to harden into a stable substance. In contrast, the group without starch began to collapse at the beginning and completely collapsed at the 60th minute. However, while these methods improved the collapse performance, the setting time, injectability and mechanical properties of the cement were not significantly improved, so a composite material is needed to solve the above problems. Summary of the invention

[0004] The present invention aims to provide a bone cement composite material with anti-disintegration performance and a preparation method thereof, which is used for repairing and treating bone defects. The bone cement composite material not only has excellent anti-disintegration performance, injectability and mechanical properties, but also can promote the attachment and proliferation of osteoblasts, and it can induce osteogenic differentiation in vitro.

[0005] The present invention improves the anti-disintegration performance of bone cement by compounding sodium alginate / carboxymethyl chitosan solidifying liquid on the basis of common calcium phosphate / calcium sulfate bone cement composite material. Sodium alginate is a natural material with good biocompatibility. Adding it can improve the biocompatibility of bone cement and reduce the stimulation to surrounding tissues; carboxymethyl chitosan is a high molecular weight polysaccharide with good water solubility and thickening properties. It can form a stable colloidal solution in cement paste, increase its viscosity, and thus improve the fluidity and handling performance of cement paste; carboxymethyl chitosan can interact with calcium ions in cement paste to delay or shorten its setting time; carboxymethyl chitosan can form a cross-linked structure with other components in bone cement or enhance the microstructure of bone cement, which helps to improve its overall strength and stability; carboxymethyl chitosan has good controlled release ability and can control the release rate of drugs or bioactive substances to a certain extent, thereby achieving the purpose of local treatment or promoting bone healing; carboxymethyl chitosan has good biodegradability and can be gradually decomposed in the body, thereby regulating the overall degradation rate of bone cement. The bone cement composite material prepared by the present invention has good biocompatibility; the gel network formed by carboxymethyl chitosan and sodium alginate significantly improves the compressive strength of bone cement, and has excellent anti-collapse performance and injectability. The mechanism of the combination of carboxymethyl chitosan, sodium alginate, α-TCP and α-CSH mainly involves the following aspects: ① hydrogen bond and electrostatic interaction: the functional groups (such as carboxyl) in carboxymethyl chitosan and sodium alginate can hydrogen bond and electrostatic interaction with the surface ions of α-TCP and α-CSH to enhance their binding force; ② cross-linking reaction: sodium alginate can form a cross-linked structure in the presence of calcium ions, which helps to improve the stability and mechanical properties of the composite material; ③ mineralization: α-TCP and α-CSH will release calcium and phosphorus in the body environment, promote the mineralization of carboxymethyl chitosan and sodium alginate, and form a more stable composite structure; ④ biological activity: the combination of these materials can improve biological activity, promote cell adhesion and proliferation, and further enhance the biological activity of the material.

[0006] The present invention provides a bone cement composite material with anti-collapse performance, including a solid phase part and a liquid phase part; the liquid phase part and the solid phase part are mixed at a liquid-to-solid ratio of 0.35 mL / g to 0.6 mL / g; the solid phase part is composed of calcium sulfate powder and calcium phosphate powder, and the mass ratio of the two is 85:15; the liquid phase part uses carboxymethyl chitosan or a combination of carboxymethyl chitosan and sodium alginate. Specifically, the sodium alginate is a SA solution with a concentration of 1 wt%; the carboxymethyl chitosan is a CMCS solution with a concentration of 1 wt% to 20 wt%; when the two are selected for combination, the volume ratio of the two is 1:1.

[0007] In the above solid phase part, the calcium sulfate (α-CSH) powder is prepared by a hydrothermal method using calcium sulfate dihydrate as a raw material, and the calcium phosphate (α-TCP) powder is synthesized by a high temperature solid phase reaction using calcium carbonate, phosphoric acid and calcium hydroxide.

[0008] The present invention provides a method for preparing the above-mentioned bone cement composite material with anti-collapse performance, comprising the following steps: (1) Preparation of α-CSH powder: Using calcium sulfate dihydrate as raw material by hydrothermal method; (2) Preparation of α-TCP powder: α-TCP powder was synthesized by high temperature solid phase reaction with calcium carbonate, phosphoric acid and calcium hydroxide. The calcium sulfate powder and calcium phosphate powder are used as the solid phase in a mass ratio of 85:15; (3) Combination of the solid phase (bone cement main body) and the liquid phase (solidifying liquid): The liquid phase and the solid phase are mixed at a liquid-to-solid ratio of 0.35 mL / g to 0.6 mL / g, and a bone cement stirring rod is used to form a uniform cement slurry to make a viscous bone cement composite material.

[0009] The liquid phase part is selected from carboxymethyl chitosan or a combination of carboxymethyl chitosan and sodium alginate.

[0010] When two solidifying liquids are selected to form the liquid phase, the method is as follows: first, dissolve an appropriate amount of SA to prepare a 1 wt% SA solution; dissolve an appropriate amount of CMCS to prepare a 1 wt%~20 wt% CMCS solution; then, add the SA solution and the CMCS solution to the bone cement in a volume ratio of 1:1.

[0011] Beneficial effects of the present invention: (1) The addition of calcium sulfate will change the crystal structure and microstructure of bone cement, thereby affecting its mechanical properties. The strength of bone cement can be optimized by adjusting the amount of calcium sulfate added. Calcium sulfate degrades too quickly, while calcium phosphate degrades over a long period of time. Adding calcium sulfate can regulate the degradation rate of bone cement composite materials, making them better suited for clinical applications in bone defect diseases.

[0012] (2) Sodium alginate can form a network-like colloidal structure during the hardening process of bone cement, which helps to improve the strength and anti-collapse performance of cement. Sodium alginate can improve its operability during injection by increasing the viscosity and fluidity of cement slurry.

[0013] (3) Carboxymethyl chitosan can interact with calcium ions in cement paste, delaying or shortening its setting time; carboxymethyl chitosan can form a cross-linked structure with other components in bone cement or enhance the microstructure of bone cement, which helps to improve its overall strength and stability; carboxymethyl chitosan has good controlled release ability and can control the release rate of drugs or bioactive substances to a certain extent, thereby achieving the purpose of local treatment or promoting bone healing; carboxymethyl chitosan has good biodegradability and can be gradually decomposed in the body, thereby regulating the overall degradation rate of bone cement.

[0014] (4) The bone cement composite material prepared by the present invention has good biocompatibility; the gel network formed by carboxymethyl chitosan and sodium alginate significantly improves the compressive strength of bone cement, and exhibits excellent anti-collapse performance and injectability; at the same time, the bone cement composite material promotes the attachment and proliferation of osteoblasts, and it can induce osteogenic differentiation in vitro; the bone cement composite material prepared by the present invention has excellent bone repair ability and can obtain better clinical effects, and can be used for the repair and treatment of bone defects, and has good application prospects for bone defect diseases. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The figure is a schematic diagram of the preparation principle of the bone cement composite material of the present invention; Figure 2It is an electron microscopic image of the bone cement composite material prepared in the comparative example and embodiments 1 to 10; in the figure (a): α-TCP / α-CSH-Con, (b): α-TCP / α-CSH-CMCS1, (c): α-TCP / α-CSH-CMCS5, (d): α-TCP / α-CSH-CMCS10, (e): α-TCP / α-CSH-CMCS15, (f): α-TCP / α-CSH-CMCS20, (g): α-TCP / α-CSH-SA-CMCS1, (h): α-TCP / α-CSH-SA-CMCS5, (i): α-TCP / α-CSH-SA-CMCS10, (j): α-TCP / α-CSH-SA-CMCS15, (k): α-TCP / α-CSH-SA-CMCS20; Figure 3 Result diagram of the setting time of the bone cement composite materials prepared in the comparative example and Examples 1 to 10; Figure 4 is a graph showing the compressive strength results of the bone cement composite materials prepared in the comparative example and embodiments 1 to 10; Figure 5 1 is a graph showing the injectability test results of the bone cement composite materials prepared in the comparative example and embodiments 1 to 10; Figure 6 1 is a graph showing the anti-collapse test results of the bone cement composite materials prepared in Examples 2 to 5 and Examples 7 to 10; Figure 7 The CCK8 test results of the bone cement composite materials prepared in the comparative example, Example 4 and Example 9; Figure 8 is the cell survival rate of the bone cement composite materials prepared in the comparative example, example 4 and example 9; Fig. 9 The ALP test results of the bone cement composite materials prepared in the comparative example, example 4 and example 9; Fig.10 These are the ARS test results of the bone cement composite materials prepared in comparative examples, namely, Example 4 and Example 9. DETAILED DESCRIPTION

[0016] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below, but the implementation methods of the present invention are not limited thereto.

[0017] Related materials involved in the embodiments: 1. The phosphoric acid, calcium carbonate, calcium hydroxide, calcium sulfate dihydrate, carboxymethyl chitosan and sodium alginate used in the examples are all commercially available chemically pure raw materials.

[0018] 2. α-tricalcium phosphate (α-TCP) (1) At room temperature, CaCO 3 Powder and H 3 PO 4 Liquid: Based on the calcium-phosphorus ratio (molar ratio) of 1.5, weigh 13.13 g of CaCO 3 and 29.98 g H 3 PO 4 (1000 mL of deionized water), mixed them and placed them in a beaker with magnetic stirring to form a suspension. After 1.5 h, Ca(HPO 4 ) 2 Solution; (2) Weigh 10.13 g Ca(OH) 2 , add 1000 mL of deionized water and stir magnetically to form a suspension. Pour the solution obtained in step (1) into a separatory funnel and slowly drip in a solution containing Ca(OH) 2 In the beaker of the suspension, continue the reaction to obtain CaHPO 4 Solution; (3) 13.13 g CaCO 3 Add to the solution obtained in the above reaction, react overnight under magnetic stirring to obtain Ca 3 (PO 4 ) 2 Solution; (4) After the reaction is completed, let it stand for 10 hours, separate the lower layer of paste-like white precipitate from the supernatant and centrifuge for 15 minutes (3000r / min); (5) Move the product into a ball mill and mill it for 2 h. After the milling is completed, centrifuge it again (3000 r / min, 15 min); (6) Transfer the white precipitate at the bottom layer into a 250 mL beaker, place it in a vacuum drying oven at 80 °C and dry it for 24 h before taking it out; (7) The dried powder needs to be ground into powder using an agate mortar and sintered in a high-temperature furnace with a set heating program. After the reaction is completed, it should be quickly removed and rapidly cooled at room temperature. (8) Grinding and sieving to obtain an α-TCP material with a particle size distribution mainly ranging from 0.13 to 0.56 μm and an average particle size of 0.21 μm.

[0019] 3. α-Calcium sulfate hemihydrate (α-CSH) It is prepared by the hydrothermal method (also known as the hot liquid method). The specific method is: weigh two portions of CSD (calcium sulfate dihydrate) with a mass of 40g respectively, press them neatly before putting them into the vertical pressure steam sterilizer, and try to place the materials in the square frame of the square plate to avoid the water vapor condensing and flowing into the materials during the reaction. The subsequent reaction is carried out under saturated steam pressure at 127℃. After the reaction is completed after 9h, it is dried in an oven at 110℃ for 2h, and then ground and sieved to obtain a white α-CSH material with fine particles.

[0020] Comparative example (the curing liquid is pure water) Pure water was used as the solidifying liquid. 2.55 g of α-CSH and 0.45 g of α-TCP powder were taken and mixed thoroughly in a stirring vessel. Pure water was added to the liquid phase and the solid phase at a liquid-to-solid ratio of 0.6 mL / g. After rapid stirring, bone cement slurry was prepared. A portion of the bone cement slurry was quickly poured into the mold, paying attention to reducing the formation of pores, and demolded after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry was placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-Con. Example 1

[0021] Prepare 1 wt% carboxymethyl chitosan solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 1 wt% carboxymethyl chitosan solution to the liquid phase and solid phase at a liquid-solid ratio of 0.6 mL: 1g. After rapid stirring, pour a portion of the bone cement slurry into the mold quickly, paying attention to reducing the formation of pores, and demold it after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-CMCS1. Example 2

[0022] Prepare 5 wt% carboxymethyl chitosan solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powders and mix them thoroughly in a stirring vessel. Add 5 wt% carboxymethyl chitosan to the solid phase and liquid phase at a liquid-to-solid ratio of 0.6 mL / g. After rapid stirring, pour a portion of the bone cement slurry into the mold quickly, pay attention to reducing the formation of pores, and demold it after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-CMCS5. Example 3

[0023] Prepare 10 wt% carboxymethyl chitosan solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powders and mix them thoroughly in a stirring vessel. Add 10 wt% carboxymethyl chitosan to the solid phase and liquid phase at a liquid-to-solid ratio of 0.6 mL / g. After rapid stirring, pour a portion of the bone cement slurry into the mold quickly, paying attention to reducing the formation of pores, and demold it after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-CMCS10. Example 4

[0024] Prepare 15 wt% carboxymethyl chitosan solidification liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powders and mix them thoroughly in a stirring vessel. Add 15 wt% carboxymethyl chitosan to the solid phase and liquid phase at a liquid-to-solid ratio of 0.6 mL / g. After rapid stirring, pour a portion of the bone cement slurry into the mold quickly, pay attention to reducing the formation of pores, and demold it after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-CMCS15. Example 5

[0025] Prepare 20 wt% carboxymethyl chitosan solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powders and mix them thoroughly in a stirring vessel. Add 20 wt% carboxymethyl chitosan to the solid phase and liquid phase at a liquid-to-solid ratio of 0.6 mL / g. After rapid stirring, pour a portion of the bone cement slurry into the mold quickly, pay attention to reducing the formation of pores, and demold it after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-CMCS20. Example 6

[0026] Prepare 1 wt% carboxymethyl chitosan solidifying liquid and 1 wt% sodium alginate solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 1 wt% carboxymethyl chitosan and 1 wt% sodium alginate solidifying liquid to the solid phase and liquid phase at a liquid-solid ratio of 0.6 mL / g. The two solidifying liquids are added in a volume ratio of 1:1. After rapid stirring, a portion of the bone cement slurry is quickly poured into the mold, paying attention to reducing the formation of pores, and demolding after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectable testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-SA-CMCS1. Example 7

[0027] Prepare 5 wt% carboxymethyl chitosan solidifying liquid and 1 wt% sodium alginate solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 5 wt% carboxymethyl chitosan and 1 wt% sodium alginate solidifying liquid to the solid phase and liquid phase at a liquid-solid ratio of 0.6 mL / g. The two solidifying liquids are added in a volume ratio of 1:1. After rapid stirring, a portion of the bone cement slurry is quickly poured into the mold, paying attention to reducing the formation of pores, and demolding after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-SA-CMCS5. Example 8

[0028] Prepare 10 wt% carboxymethyl chitosan solidifying liquid and 1 wt% sodium alginate solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 10 wt% carboxymethyl chitosan and 1 wt% sodium alginate solidifying liquid to the solid phase and liquid phase at a liquid-solid ratio of 0.6 mL / g. The two solidifying liquids are added in a volume ratio of 1:1. After rapid stirring, a portion of the bone cement slurry is quickly poured into the mold, paying attention to reducing the formation of pores, and demolding after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-SA-CMCS10. Example 9

[0029] Prepare 15 wt% carboxymethyl chitosan solidifying liquid and 1 wt% sodium alginate solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 15 wt% carboxymethyl chitosan and 1 wt% sodium alginate solidifying liquid to the solid phase and liquid phase at a liquid-solid ratio of 0.6 mL / g. The two solidifying liquids are added in a volume ratio of 1:1. After rapid stirring, a portion of the bone cement slurry is quickly poured into the mold, paying attention to reducing the formation of pores, and demolding after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectability testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-SA-CMCS15. Example 10

[0030] Prepare 20 wt% carboxymethyl chitosan solidifying liquid and 1 wt% sodium alginate solidifying liquid. Take 2.55 g α-CSH and 0.45 g α-TCP powder and mix them thoroughly in a stirring vessel. Add 20 wt% carboxymethyl chitosan and 1 wt% sodium alginate solidifying liquid to the solid phase and liquid phase at a liquid-solid ratio of 0.6 mL / g. The two solidifying liquids are added in a volume ratio of 1:1. After rapid stirring, a portion of the bone cement slurry is quickly poured into the mold, paying attention to reducing the formation of pores, and demolding after solidification to prepare bone cement columns and bone cement particles for mechanical experiments and cell experiments; the other part of the bone cement slurry is placed in a 2.5 ml syringe with a diameter of 2.0 mm with a stirring spoon for injectable testing and anti-collapse experiments. The sample obtained in this example is marked as α-CSH / α-TCP-SA-CMCS20.

[0031] Figure 2is an electron microscope image of the bone cement composite material prepared in the comparative example and embodiments 1 to 10; Figure 2 It can be observed that the surface of the bone cement composite material is mainly composed of rod-shaped α-CSH, granular α-TCP and plate-like crystals that generate CSD. When CMCS and SA are added, it can be observed that the surface presents a porous structure, making the bone cement aggregation more dense.

[0032] Figure 3 It is the result of the setting time of the bone cement composite material prepared by the comparative example and Examples 1 to 10, and the setting time of Con is 30.41 ± 1.01 minutes. After adding CMCS, the setting time increases significantly, and increases with the increase of CMCS concentration. The setting time of the bone cement composite material with CMCS added alone exceeds 30min, which will have an adverse effect on clinical application. When CMCS is dissolved in water, it will significantly increase the viscosity of the solution, thereby delaying the diffusion rate of water in α-CSH and α-TCP particles. When the diffusion rate of water slows down, the speed of the hydration reaction and the curing process will also decrease, resulting in an increase in the setting time. When SA is introduced, the setting time of the bone cement composite material is less than 30min, and when the CMCS content is 15%, the setting time is 13.6 ± 0.46min. When CMCS and SA are added together, the synergistic effect of the two can optimize the solution viscosity, promote interfacial reaction, increase the release and complexation of calcium ions, and form a more stable network structure, thereby accelerating the hydration reaction and the setting process and shortening the setting time.

[0033] Figure 4 The compressive strength results of the bone cement composites prepared in the comparative examples and Examples 1 to 10 show that with the addition of CMCS, the compressive strength of the bone cement composites is significantly improved compared with the control group, and with the increase of CMCS concentration, the compressive strength gradually increases. When the CMCS content is 15%, the mechanical strength is the highest, reaching 12.48±1.1 MPa. The compressive strength of the SA group reaches the highest at α-CSH / α-TCP-SA-CMCS15, which is 11.53±1.3 MPa, while it drops to 7.63±0.8MPa at α-CSH / α-TCP-SA-CMCS20. It shows that the appropriate addition of CMCS and SA can improve the compressive strength of α-TCP and α-CSH bone cement composites by improving the microstructure and enhancing the interface bonding force.

[0034] Figure 5The results of the injectability of the bone cement composites prepared in the comparative example and Examples 1 to 10 are shown. The injectability of the two groups of samples (containing SA and excluding SA) starts from 50.9±0.36%. At a low CMCS concentration (1%), the injectability of the SA-free group slightly increases to about 58.5±0.26%, while the injectability of the SA-containing group significantly decreases to about 7.93±0.75%. Under the action of a medium CMCS concentration (5%), the injectability of both groups of samples is significantly improved. Under the action of a high CMCS concentration (10% to 20%), the injectability of the SA-free group reaches 94.13±0.5%, 95.47±0.55% and 95.7±1.65%, respectively; the injectability of the SA-containing group reaches 96±0.26%, 95.7±0.44% and 95.9±0.71%, respectively. The bone cement composite has excellent injectability at higher concentrations.

[0035] Figure 6 The results are the anti-collapse results of the bone cement composite materials prepared in Examples 2 to 5 and Examples 7 to 10. Since Con and α-CSH / α-TCP-CMCS1 have poor injectability, the anti-collapse properties of the remaining bone cement composite materials were studied. Figure 6 As shown in A, the bone cement composite material did not collapse after being left to stand for 30 minutes after extrusion, indicating that the addition of CMCS can improve the anti-collapse performance of the bone cement composite material. Figure 6 B is a further study on the anti-collapse performance of bone cement composites placed in a dynamic environment. It was found that the bone cement composites without the introduction of SA collapsed, while after the introduction of SA, the bone cement composites maintained a good morphology and did not collapse. This shows that the gel network formed by SA and CMCS increases the cohesion and viscosity of the bone cement composite, making the mixture more stable and not easy to collapse, thus improving the anti-collapse performance.

[0036] Figure 7 This is the result of CCK8 test on the bone cement composites prepared in Example 4 and Example 9, which is the cell proliferation of Blank, Con, CMCS, and SA / CMCS after 1, 3, and 5 days of culture. The results show that the cell survival rates of each group are similar on the first day, and the cells of each group show good cell proliferation characteristics on the third day. The OD values ​​of each group increased on the fifth day, indicating that the cell survival rate increased with the passage of time. The cell survival rate of the SA / CMCS15 group increased by 3% compared with the Blank group, and increased by 14% and 13% compared with the Con group and CMCS group, respectively, which is higher than other sample groups, showing better biocompatibility. It also shows that the addition of SA and CMCS is more conducive to the growth and proliferation of cells.

[0037] Figure 8The RGR of each group on the fifth day was calculated, and its cytotoxicity was analyzed. The values ​​of each group were greater than 80%, and their toxicity levels were all level 1. This shows that the bone cement composite material has good cell compatibility and its cytotoxicity to MC3T3 is negligible. In addition, the RGR value of the SA / CMCS15 group was higher than that of the Blank group. Both CMCS and SA are natural polymer materials with good biocompatibility and can promote cell proliferation and differentiation.

[0038] Fig. 9 The results of the ALP test of the bone cement composites prepared in Example 4 and Example 9 are shown in Table 1. The OD value of the Blank group is 0.073, and as the blank control group, its ALP activity is the lowest; the OD value of the Con group is slightly higher than that of the Blank group, which is 0.078, indicating that the control group is slightly improved relative to the blank group, but there is no significant difference; the OD value of the CMCS15 group is close to 0.091, which is significantly higher than that of the Blank group (p<0.01), indicating that CMCS15 has a certain promoting effect on ALP activity and is beneficial to the differentiation of osteoblasts; among them, the OD value of the SA / CMCS15 group reaches the highest, close to 0.1, indicating that this group has the strongest promoting effect on ALP activity. Compared with the blank group and the control group, both the CMCS15 and SA / CMCS15 groups significantly increased the ALP activity, indicating that the material is helpful for the differentiation of osteoblasts. CMCS has good biocompatibility and biological activity, and can promote the adhesion and differentiation of osteoblasts, so the ALP activity of the CMCS15 group is higher. SA can further improve the material microenvironment, making it easier for cells to grow, while providing a good ion exchange environment to enhance the osteogenic activity of cells. In summary, the synergistic effect of CMCS and SA significantly increased ALP activity.

[0039] Fig.10 It is a comparative example. The results of the alizarin red test of the bone cement composites prepared in Example 4 and Example 9 show that orange-red mineralized nodules appear in the cells under the microscope. There are basically no mineralized nodules in the Blank group, and there is no orange-red calcium deposition; there are relatively few mineralized nodules in the Con group, which are evenly distributed orange-red circles or ovals, with relatively light colors and clear outlines; the CMCS15 group has a larger area of ​​mineralized nodules, more nodules, and is widely dispersed, and the color is also darker than the Blank and Con groups; while in SA / CMCS15, there are a large number of mineralized nodules, a large area, a high density, and a large area of ​​deep staining. The overall number of calcified nodules and the mineralized area also show a trend of gradually increasing. Therefore, in this experiment, the bone cement composite material SA / CMCS15 group showed a certain promoting effect on osteogenic induction, and had a positive effect on the osteogenic differentiation of cells.

[0040] Table 1 Liquid content of composite materials

[0041] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the protection scope of the present invention.

Claims

1. A bone cement composite material with anti-collapse performance, characterized in that: It includes a solid phase part and a liquid phase part; The liquid phase and the solid phase are mixed at a liquid-to-solid ratio of 0.35 mL / g to 0.6 mL / g; the solid phase is composed of calcium sulfate powder and calcium phosphate powder, and the mass ratio of the two is 85:15; the liquid phase is selected from carboxymethyl chitosan or a combination of carboxymethyl chitosan and sodium alginate.

2. The bone cement composite material with anti-collapse performance according to claim 1, characterized in that: The sodium alginate is a SA solution with a concentration of 1 wt%; the carboxymethyl chitosan is a CMCS solution with a concentration of 1 wt% to 20 wt%; when the two are selected for combination, the volume ratio of the two is 1:

1.

3. The bone cement composite material with anti-collapse performance according to claim 1, characterized in that: In the solid phase part, the calcium sulfate powder is prepared by a hydrothermal method using calcium sulfate dihydrate as a raw material, and the calcium phosphate powder is synthesized by a high-temperature solid phase reaction using calcium carbonate, phosphoric acid and calcium hydroxide.

4. A method for preparing a bone cement composite material with anti-collapse performance according to any one of claims 1 to 3, characterized in that The steps include: (1) Preparation of α-CSH powder: Using calcium sulfate dihydrate as raw material by a hydrothermal method; (2) Preparation of α-TCP powder: α-TCP powder is synthesized by high temperature solid phase reaction with calcium carbonate, phosphoric acid and calcium hydroxide, wherein the calcium sulfate powder and calcium phosphate powder constitute the solid phase in a mass ratio of 85:15; (3) Mixing the solid phase and the liquid phase: The liquid phase and the solid phase are mixed at a liquid-to-solid ratio of 0.35 mL / g to 0.6 mL / g, and a bone cement stirring rod is used to form a uniform cement slurry to prepare a viscous bone cement composite material.

5. The method for preparing the bone cement composite material with anti-collapse performance according to claim 4, characterized in that: The liquid phase part is selected from carboxymethyl chitosan or a combination of carboxymethyl chitosan and sodium alginate.

6. The method for preparing the bone cement composite material with anti-collapse performance according to claim 5, characterized in that: When two solidifying liquids are selected to form the liquid phase, the method is as follows: first, dissolve SA to prepare a 1 wt% SA solution; dissolve CMCS to prepare a 1 wt%~20 wt% CMCS solution; then, add the SA solution and the CMCS solution to the bone cement in a volume ratio of 1:

1.

7. The method for preparing the bone cement composite material with anti-collapse performance according to claim 4, characterized in that: The preparation method of α-TCP powder is as follows: (1) At room temperature, CaCO3 powder and H3PO4 liquid were diluted with 13.13 g CaCO3 and 29.98 g H3PO4 according to the calcium-phosphorus molar ratio of 1.

5. After mixing, they were placed in a beaker and stirred magnetically to form a suspension. After 1.5 hours, Ca(HPO4)2 solution was obtained. (2) Weigh 10.13 g of Ca(OH)2, add 1000 mL of deionized water and stir magnetically to form a suspension. Pour the solution obtained in step (1) into a separatory funnel and slowly drip it into the beaker containing the Ca(OH)2 suspension. Continue the reaction to obtain a CaHPO4 solution. (3) Add 13.13 g of CaCO3 to the solution obtained in the above reaction and react overnight under magnetic stirring to obtain a Ca3(PO4)2 solution; (4) After the reaction is completed, let it stand for 10 hours, separate the lower layer of paste-like white precipitate from the supernatant and centrifuge for 15 minutes at 3000 r / min; (5) Move the mixture into a ball mill and mill it for 2 h. After the milling is completed, centrifuge it again for 15 min at 3000 r / min. (6) Transfer the white precipitate at the bottom layer into a 250 mL beaker, place it in a vacuum drying oven at 80 °C and dry it for 24 h before taking it out; (7) The dried powder needs to be ground into powder using an agate mortar and sintered in a high-temperature furnace with a set heating program. After the reaction is completed, it should be quickly removed and rapidly cooled at room temperature. (8) Grinding and sieving to obtain an α-TCP material with a particle size distribution mainly ranging from 0.13 to 0.56 μm and an average particle size of 0.21 μm.

8. The method for preparing the bone cement composite material with anti-collapse performance according to claim 4, characterized in that: The preparation method of α-CSH powder is as follows: weigh two portions of 40 g of calcium sulfate dihydrate respectively, press them neatly before putting them into a vertical pressure steam sterilizer, and try to place the material in the square frame of the square plate; the reaction is carried out under saturated steam pressure at 127°C, and after the reaction is completed after cooling for 9 hours, it is dried in an oven at 110°C for 2 hours, and then ground and sieved to obtain white α-CSH material with fine particles.

Citation Information

Patent Citations

  • Anti-collapse calcium-silicon-based composite bone cement as well as preparation method and application thereof

    CN106693063A

  • Calcium sulfate hemihydrate / octacalcium phosphate / carboxymethyl chitosan composite artificial bone material and preparation method thereof

    CN106938056A

  • Micro-nano-scale silk fibroin induced bone mineralization calcium phosphate-based bone cement and preparation method thereof

    CN113559315A

  • Composite bone cement as well as preparation method and application thereof

    CN115634319A

  • Bone recycled material kit, pasty bone recycled material, bone recycled material and bone binder

    JP2020069216A

Cited By

  • Composite bone cement as well as preparation method and application thereof

    CN121197522A